8 UMPSA students selected in Axiata Digital Leadership Program for Girls 2024 - Naqiah, Puaad (UMPSA, 2024)
BANGI, 20 May 2024 - A total of eight Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) students were selected to represent the university in the Axiata Digital Leadership Programme for Girls 2024 organised by the Axiata Foundation.